Experimental and Analytical Investigation of Flexural Behavior of Carbon Nanotube Reinforced Textile Based Composites - Madenci E.; zk?l? Y.O.; Aksoylu C.; Asyraf M.R.M.; Syamsir A.; Supian A.B.M.; Elizaveta B. (MDPI, 2024)
In this study, the main goal of this study was to understand the effect of carbon nanotube (CNT) additives on the elastic behaviors of textile-based composites. The materials have three phases: carbon fiber fabric, epoxy matrix, and carbon nanotubes. Different weight fractions of CNTs were used (0% as a reference, 0.3%). Mechanical tests were performed, such as tension and three-point bending beam tests. In addition, the composite material damages were examined in detail. The experimental results show that the samples with CNT carried 9% and 23% more axial tensile force and bending capacity on average than those with NEAT. Besides, it was understood that adding 0.3% by weight of MWCNT increases the tensile modulus by approximately 9%. Finally, the mechanical tensile and bending tests are supported by analytical solutions successfully applied in the literature. 2023 by the authors.